Aldehyde Dehydrogenase 2 rs671 Polymorphism is Associated with Susceptibility of Coronary Atherosclerosis in Patients with Hypertension - Hou H; Huang S; Huang W; Huang L; Zhang Z; Liang L (International Journal of General Medicine)
Haisong Hou,1 Sina Huang,2 Wenyi Huang,3 Lingmei Huang,1 Zhouhua Zhang,4 Liu Liang5 1Department of Blood Transfusion, Meizhou People’s Hospital, Meizhou, People’s Republic of China; 2Department of Cardiovascular Surgery, Meizhou People’s Hospital, Meizhou, People’s Republic of China; 3Center for Surgical Operation, Meizhou People’s Hospital, Meizhou, People’s Republic of China; 4Center for Cardiovascular Diseases, Meizhou People’s Hospital, Meizhou, People’s Republic of China; 5Department of Laboratory Medicine, Meizhou People’s Hospital, Meizhou, People’s Republic of ChinaCorrespondence: Haisong Hou, Department of Blood Transfusion, Meizhou People’s Hospital, Meizhou, People’s Republic of China, Email houhaisonggd6@163.comObjective: Predisposing factors for coronary atherosclerosis in hypertensive individuals are unclear. Atherosclerosis is a chronic inflammatory disease caused by lipid deposition in the blood vessels, and aldehyde dehydrogenase 2 (ALDH2) is involved in this process. The aim of this study was to assess the relationship between ALDH2 rs671 polymorphism, serum lipids, peripheral inflammation indices (pan-immune inflammation value (PIV), systemic immune inflammation index (SII), and system inflammation response index (SIRI)) and coronary atherosclerosis risk in hypertensive patients.Methods: A total of 923 patients with hypertension (439 patients with coronary atherosclerosis, and 484 without) who were admitted to Meizhou People’s Hospital between January 2019 and February 2024 were retrospectively analyzed. The relationship between ALDH2 rs671 polymorphism, serum lipid levels, and peripheral inflammation indices and the risk of coronary atherosclerosis was analyzed.Results: There were 532 (57.6%), 337 (36.5%), and 54 (5.9%) individuals with ALDH2 rs671 G/G, G/A, and A/A genotype, respectively. The frequency of the ALDH2 rs671 G/A genotype, and the levels of TC, LDL-C, PIV, SII, and SIRI in patients with coronary atherosclerosis were higher than those in controls. Logistic analysis showed that body mass index (BMI) ≥ 24.0 kg/m2 (odds ratio (OR): 1.670, 95% confidence interval (CI): 1.185– 2.352, p=0.003), history of smoking (OR: 2.024, 95% CI: 1.263– 3.243, p=0.003), ALDH2 rs671 G/A genotype (OR: 1.821, 95% CI: 1.280– 2.589, p=0.001), high TC (OR: 1.592, 95% CI: 1.021– 2.485, p=0.040), high SII (OR: 2.290, 95% CI: 1.386– 3.784, p=0.001), and high SIRI (OR: 1.727, 95% CI: 1.126– 2.650, p=0.012) were associated with coronary atherosclerosis in patients with hypertension.Conclusion: Overweight (BMI ≥ 24.0 kg/m2), history of smoking, ALDH2 rs671 G/A genotype, high TC, SII, and SIRI levels were associated risk factors for coronary atherosclerosis in patients with hypertension.Keywords: coronary atherosclerosis, hypertension, ALDH2, systemic immune inflammation index, system inflammation response index